Cloning and characterisation of the Schizosaccharomyces pombe rad8 gene, a member of the SNF2 helicase family. - Doe, C L (1993)
The Schizosaccharomyces pombe rad8 mutant is sensitive to both UV and gamma irradiation. We have cloned the rad8 gene by complementation of the UV sensitivity of a rad8.190 mutant strain. The gene comprises an open reading frame of 3.4 kb which does not contain any introns and is capable of encoding a 1133 amino acid protein of 129 kDa. Deletion of the gene indicates that it is not essential for cell viability. Recognisable motifs are present for a nuclear localisation signal, a RING finger and helicase domains. The predicted protein is a member of the SNF2 subfamily of proteins and shows particular homology to the Saccharomyces cerevisiae RAD5 protein. Double mutant analysis demonstrated that the rad8 mutant is not epistatic to mutants in the excision repair pathway (rad13) or checkpoint pathway (rad9). Analysis of radiation sensitivity though the cell cycle indicates that, unlike most other rad mutants, rad8 is most sensitive to irradiation during the G1/S period.